Effect of adenotonsillectomy on otitis media with effusion - Ojimadu, Chinwe I.; Edevbie, Ifeoma C.; Ojetoyinbo, Adedoja A.; Undie, Nseobong B.; Imogu, Andrew O.; Olusesi, Abiodun D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Otitis media with effusion (OME) is a common cause of childhood hearing loss. In children, it may co-exist with adenotonsillar enlargement. In such cases, adenotonsillectomy combined with myringotomy and tympanostomy tube insertion is the standard surgical treatment approach worldwide. This study however, investigated whether adenotonsillectomy alone can resolve OME in children with concurrent adenotonsillar disease, with implications for reducing surgical morbidity and healthcare expenditures. Methods: This prospective pre-test-post-test study was conducted at the Department of Otolaryngology, National Hospital Abuja, Nigeria. Ninety-five children (aged 1-8 years) with adenotonsillar hypertrophy and preoperative tympanogram types B or C underwent adenotonsillectomy. Tympanometric evaluations were performed at baseline (2 weeks preoperatively) and 6 weeks postoperatively to assess changes in middle ear function. Results: Pre-operative tympanometry identified OME in 166 ears. Post-operative tympanometry at 6 weeks demonstrated resolution of OME (type B or C to type A tympanogram) in 88 ears (53%, χ2=22.5, p=0.001) which was statistically significant. Among the remaining 78 ears, 41 (24.7%) showed no change, while 37 ears demonstrated changes to alternative tympanogram types, (B to C, C2 to C1, B/C to as), which was considered a partial improvement (resolving OME, but not complete resolution). Conclusions: Findings from this study suggest that adenotonsillectomy alone may resolve otitis media with effusion (OME) in children with coexisting adenotonsillar hypertrophy, with significant improvements observed at a minimum follow-up of 6 weeks.